Genetically determined syndromes associated with premature aging - Nedoszytko, Bogusław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Syndromes involving premature aging provide outstanding models for a better understanding of both skin senescence and of the aging process in general. Based on the molecular pathomechanisms several main subsets of such disorders can be distinguished: progeroid syndromes with dysfunction of proteins forming the nuclear envelope (Hutchinson-Gilford syndrome, Werner syndrome, lipodystrophy), syndromes involving dysfunction of the nucleotide excision/repair DNA system (xeroderma pigmentosum, Cockayne syndrome), dysfunctions of helicases – enzymes of replication and transcription (Werner, Rothmund-Thomson, Bloom syndromes and ataxia telangiectasia), mutations of genes encoding proteins of extracellular matrix (variants of Ehlers-Danlos, and cutis laxa syndromes), mutations of the genes encoding telomerase complex (dyskeratosis congenita), and a syndrome with chromosomal aberrations (Down syndrome). Recent advances in basic research have raised new hopes regarding targeted therapies with progeria and aging. Key words: premature aging syndromes, nuclear envelope, DNA repair, telomeres, genomic instability, cancer.